Responsible Regulation of Artificial Intelligence in the Legal Profession Through a Split Bar: Implications for Legal Educators - S.I. Strong (Washington University Journal of Law and Policy, 2026)
Artificial intelligence (AI), particularly generative AI, poses a number of unique challenges to the legal profession and legal education. As discussed in numerous empirical studies, generative AI negatively affects the performance of both students and knowledge workers, causing harm to both individuals and society at large. This is not to say that generative AI does not have its benefits. Indeed, AI’s ability to reduce time and costs has led many people within the legal profession to become so enamored of AI that it is impossible to envision a future without automation. Given these realities, it would be futile to propose the elimination of generative AI from the justice sector. Instead, the goal of the legal profession and of this Essay must be to find a way to maximize the appropriate use of generative AI in law while minimizing the dangers to human autonomy and creativity. Even a cursory analysis of the extent and nature of the dangers of generative AI suggests that simply tweaking existing systems will not be enough. Instead, fundamental reforms of the legal profession and legal education are needed to ensure that adequate protections are in place. This Essay proposes a new way of structuring both the legal profession and legal education, building on time-tested techniques used in England while incorporating modifications that take the special nature of generative AI into account. In so doing, the proposal contained herein not only complies with cautions enunciated by empirical scholars concerning the use of generative AI, it also takes the legal profession and legal education into the twenty-first century in a logical and responsible manner.
Keywords: #ResponsibleAILaw; #StructuralAISafeguards; #AICreativityCrisis; #EmpiricalAIStudies; #LegalProfessionReform; #GenAIRisks